Economical Production of Phenazine-1-carboxylic Acid from Glycerol by Pseudomonas chlororaphis Using Cost-Effective Minimal Medium - Yu-Xuan Li; Sheng-Jie Yue; Yi-Fan Zheng; Peng Huang; Yan-Fang Nie; Xiang-Rui Hao; Hong-Yan Zhang; Wei Wang; Hong-Bo Hu; Xue-Hong Zhang (Biology, 2023)
Phenazine compounds are widely used in agricultural control and the medicine industry due to their high inhibitory activity against pathogens and antitumor activity. The green and sustainable method of synthesizing phenazine compounds through microbial fermentation often requires a complex culture medium containing tryptone and yeast extract, and its cost is relatively high, which greatly limits the large-scale industrial production of phenazine compounds by fermentation. The aim of this study was to develop a cost-effective minimal medium for the efficient synthesis of phenazine compounds by Pseudomonas chlororaphis. Through testing the minimum medium commonly used by Pseudomonas, an ME medium for P. chlororaphis with a high production of phenazine compounds was obtained. Then, the components of the ME medium and the other medium were compared and replaced to verify the beneficial promoting effect of Fe2+ and NH4+ on phenazine compounds. A cost-effective general defined medium (GDM) using glycerol as the sole carbon source was obtained by optimizing the composition of the ME medium. Using the GDM, the production of phenazine compounds by P. chlororaphis reached 1073.5 mg/L, which was 1.3 times that achieved using a complex medium, while the cost of the GDM was only 10% that of a complex medium (e.g., the KB medium). Finally, by engineering the glycerol metabolic pathway, the titer of phenazine-1-carboxylic acid reached the highest level achieved using a minimum medium so far. This work demonstrates how we systematically analyzed and optimized the composition of the medium and integrated a metabolic engineering method to obtain the most cost-effective fermentation strategy.